Principles and practice of surgery - Garden, O. James; Bradbury, A. W. (Andrew Walter), 1961-; Forsythe, John L. R. (Churchill Livingstone, 2002)
Learning about specific diseases that are usually treated with surgery, as well as understanding the principles of managing surgical patients, is integral to the medical curriculum and an essential precursor to the study of operative surgery. This book presents these key topics and familiarises students with surgical processes and protocols.